Proposed beach resort hotel at Desaru, Johor Darul Takzim / Mohamed Saburi Azirun - Azirun, Mohamed Saburi (1988)
It is expected that the proposed beach resort in Desaru will be the first of its kind in the southern region of Peninsular Malaysia and even the whole country. It is proposed to promote tourism and hoped to be recognised as the most favourable and popular beach resort in this region. The Lembaga Kemajuan Johor Tenggara or KEJORA has accepted the plan as the objective to create a natural environment and upgrade the standard of living of the residents there shall be achieved. The careful design consideration and the systematic approaches towards formulating the required brief renders the success of the design. The architectural images created is being derived from the existing modern buildings and the perception on what Malaysian Identity is Keindahan Semulajadi, rekabentuk berunsur Tropika,' which is the central theme of the whole development is being reinforced very well.